2015
DOI: 10.1038/mt.2015.119
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Engineered With Chimeric Antigen Receptors Targeting NKG2D Ligands Display Lethal Toxicity in Mice

Abstract: Ligands for the NKG2D receptor are overexpressed on tumors, making them interesting immunotherapy targets. To assess the tumoricidal properties of T cells directed to attack NKG2D ligands, we engineered murine T cells with two distinct NKG2D-based chimeric antigen receptors (CARs): (i) a fusion between the NKG2D receptor and the CD3ζ chain and (ii) a conventional second-generation CAR, where the extracellular domain of NKG2D was fused to CD28 and CD3ζ. To enhance the CAR surface expression, we also engineered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 56 publications
1
47
1
Order By: Relevance
“…However, a very serious concern with enhanced NKG2D CAR T cells is that NKG2DLs can be expressed on non-tumour tissues, which might cause autoimmune reactions. Indeed, a recent study reported that NKG2D CARs transduced into mouse T cells induced rapid lethal toxicity when adoptively transferred into an autologous mouse model 171 . As yet, there is limited experience in vivo with CAR-engineered NK cells to know the efficacy versus toxicity outcomes of this strategy.…”
Section: Using Nk Cells For Cancer Therapymentioning
confidence: 99%
“…However, a very serious concern with enhanced NKG2D CAR T cells is that NKG2DLs can be expressed on non-tumour tissues, which might cause autoimmune reactions. Indeed, a recent study reported that NKG2D CARs transduced into mouse T cells induced rapid lethal toxicity when adoptively transferred into an autologous mouse model 171 . As yet, there is limited experience in vivo with CAR-engineered NK cells to know the efficacy versus toxicity outcomes of this strategy.…”
Section: Using Nk Cells For Cancer Therapymentioning
confidence: 99%
“…However, this does not rule out initiation of lesions at earlier time points. Previous studies that observed toxicity in murine models of CAR therapy targeting fibroblast activating protein 49 and NKG2D ligands 50 report treatment-mediated pathology within days post T-cell transfer. The differences in kinetics seen in our study may have occurred for several reasons including differences in CAR T-cell dose, preconditioning regimes, distribution of target antigen in normal tissue, and murine strain variability.…”
Section: Model To Interrogate Questions Addressing B7-h4's Function Amentioning
confidence: 99%
“…Other models of CAR-mediated toxicity in mice tend to cause acute toxicity. 49,50 Our B7-H4 CAR model of toxicity could provide a unique preclinical model to evaluate safety approaches designed to limit long-term CAR-mediated toxicity following antitumor activity in vivo. Additionally, these studies reveal the endogenous expression pattern of B7-H4, advancing our understanding of the molecule and fostering intelligent design of novel B7-H4-specific therapeutics for the clinic.…”
Section: Model To Interrogate Questions Addressing B7-h4's Function Amentioning
confidence: 99%
“…With the development of the "humanized mouse" model 18,19 , the TCR retrogenic could further be expanded utilizing cloned human TCRs. Additionally, the 2A linked constructs can also be used to study other multi-proteins including the CD3 chains, interleukins and chimeric antigen receptors [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%